Analisis Kualitas Pelayanan Publik di Era Digital: Implementasi dan Tantangan - Jackson Yumame (Bulletin of Community Engagement, 2024)
The digital era brings transformation in various aspects of life, including in public services. This analysis investigates the quality of public services in the digital era with a focus on implementation and challenges faced. The implementation of information and communication technology is believed to be able to improve the efficiency and effectiveness of public services, facilitate accessibility for the public, and simplify various administrative procedures. However, the success of this digital transformation depends on various factors such as the availability of technological infrastructure, cybersecurity, and the digital competence of government employees. Despite the great potential, the implementation of digital services is also faced with various challenges. One of the main challenges is the digital divide, which can hinder equitable access for the entire community. In addition, the lack of public participation in the digital service development process can reduce the relevance and effectiveness of the services provided. Therefore, a comprehensive and inclusive strategy is needed to address these challenges and maximise the benefits of digital technology in improving the quality of public services. Successful digital transformation will bring significant improvements to public services, providing greater and more equitable benefits to society